Lactobacillus sakei CRL1862 improves safety and protein hydrolysis in meat systems - Castellano, Patricia Haydee (2012)
Aims The capacity of Lactobacillus sakei CRL1862 to prevent the growth of pathogens and its ability to degrade sarcoplasmic and myofibrillar proteins in pork meat systems was evaluated. In addition, basic safety aspects of Lact. sakei CRL1862 such as production of biogenic amines and antibiotic susceptibility were addressed. Methods and Results The bacteriocin-producing Lact. sakei CRL1862 showed respectively bactericide and bacteriostatic effect against Listeria monocytogenes and Staphylococcus aureus in beaker sausage assay during 9 days of storage at 22°C. The hydrolytic effect of Lact. sakei CRL1862 on protein extracts was evaluated by SDS-PAGE and reverse phase HPLC. A more pronounced proteolysis was evidenced in inoculated sarcoplasmic proteins compared with myofibrillar extracts with the generation of predominantly hydrophilic peptides and increase of total free amino acids concentration. Lactobacillus sakei CRL1862 produced neither histamine nor tyrosine and exhibited no resistance to the antibiotics assayed. Conclusions Lactobacillus sakei CRL1862 effectively controlled the growth of L. monocytogenes and Staph. aureus; moreover, it was able to hydrolyse pork meat extracts generating peptides and amino acids, which may improve hygienic and sensorial attributes of fermented meat products. Significance and Impact of the Study The use of an integrated approach to evaluate the major traits of Lact. sakei CRL1862 showed it can be applied as an autochthonous functional starter in meat fermentation.